Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Kandang Kopi Tasikmalaya - Monika Sutarsa; Arip Budiman; Yudi Kurniadi (LPPM POLITEKNIK LP3I BANDUNG, 2022)
This project aims to see the effect of price and service quality on consumer satisfaction. The independent variable used is a sample of the variables used is standard operating procedures. The population in this project is members or consumers who come more than twice to use with a total of 50 consumers. The data collection technique was carried out using a study questionnaire, while the data analysis technique was using SPSS. The results of this study conclude that price and service quality have a positive and significant effect on consumer satisfaction at Kandang Kopi